Strategic consolidation under formula apportionment - Thiess Buettner; Nadine Riedel; Marco Runkel (Center for Economic Studies and ifo Institute (CESifo), 2008)
This paper argues that profit-shifting activities of multi-jurisdictional enterprises (MJE) are maintained under a tax system of consolidation and formula apportionment (FA). A theoretical model discusses how an MJE can exploit its impact on the definition of the consolidated group strategically. The analysis shows that the MJE will run individual affiliates as separate un-consolidated firms for tax purposes if intra-group tax-rate differences, and thereby potential gains from profit-shifting, are large. We test this prediction using confidential firm-level tax-return data for the local business tax in Germany. The identification strategy exploits a quasi experiment derived from a major company tax reform in 2001 that reduced the costs associated with separating out individual affiliates. Our results show that, evaluated at the sample mean, an increase in the tax-rate variance among the MJE's affiliates by one standard deviation reduces the number of consolidated affiliates by 20%.
Keywords: H32; H73; 330; Corporate taxation; formula apportionment; micro data; Körperschaftsteuer; Steuerreform; Formula Apportionment; Steuerwirkung; Multinationales Unternehmen; Gewinnverlagerung; Deutschland